Training of young service providers and extension agents in RiceAdvice - Ahouanton, Kokou; Guindo, Samuel; Dossou-Yovo, Elliott Ronald (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
As part of the AICCRA project activities, the Syngenta Foundation and AfricaRice organized a training session for young service providers and extension agents on the use of RiceAdvice and KoboCollect. The training took place on July 21 and 22, 2022, in Ségou, in the conference room of the Gabriel Cisse Center, and was attended by 43 participants from the Center for Mechanized Agriculture of Socouma, Koumase, Gneleni, Senekasabati, Dunkafa, Wassa, and Togou. The workshop provided young service providers and extension agents with enhanced knowledge and skills in advisory services, data collection, and processing for climate-informed and locally relevant decision-making.